2023
DOI: 10.3390/ma16165639
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Analysis of Thermal and Thermodynamic Aspects of Grain Refinement of Aluminum-Silicon-Based Alloys

Abstract: The present analysis addresses the solidification and thermodynamic parameters involved during the solidification of aluminum (Al)-based alloys as presented in the literature using different systems viz., binary aluminum-boron (Al-B) and aluminum-titanium (Al-Ti) systems, ternary aluminum-titanium-boron (Al-Ti-B) and aluminum-titanium-carbon (Al-Ti-C) systems, as well as taking into consideration the silicon-titanium-aluminide (Si-TiAl3) interaction in Al-based alloys containing Si. The analysis is supported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Moreover, the literature also discusses solution treating, quenching, and artificial aging of the microstructure and on mechanical behavior [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. These articles were probably written because Al-Si-based alloys exhibit excellent castability and affordability and have a low coefficient of thermal expansion and attractive mechanical properties, making them suitable for manufacturing wheels by casting [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the literature also discusses solution treating, quenching, and artificial aging of the microstructure and on mechanical behavior [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. These articles were probably written because Al-Si-based alloys exhibit excellent castability and affordability and have a low coefficient of thermal expansion and attractive mechanical properties, making them suitable for manufacturing wheels by casting [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the microstructural characteristics are influenced by the presence of α-Al dendrites and lamellar eutectic Si [7]. It is widely recognized that a typical as-cast microstructural array affects the resulting properties [6][7][8][9][10][11][12][13][14][15]. When coarse Al and interdendritic Si particles are constituted, the reached ductility is considerably decreased [6][7][8][9][10][11][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that 7075 alloy, 7075 alloy + Zr, or 7075 alloy + Sc + Zr alloys offer better mechanical properties caused by the precipitation of Al 3 (Sc, Zr) dispersoids [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…They are the reason for the low mechanical properties of alloys. For many years, a number of technological procedures have been known to refine the microstructure and, at the same time, increase the mechanical properties resulting from the microstructure [12][13][14][15][16][17][18][19][20][21][22]. Hypoeutectic silumins are one of the few alloys in which, as a result of changes in the microstructure, it is possible to increase all mechanical properties, e.g., tensile strength and elongation, at the same time.…”
Section: Introductionmentioning
confidence: 99%